Editorial: evolution of GLP‐1 receptor agonists as pharmacotherapy for NASH beyond diabetes mellitus and obesity – authors' reply. Issue 11 (6th November 2021) - Flint, Anne; Andersen, Grit; Hockings, Paul; Plum‐Mörschel, Leona; Loomba, Rohit
LINKED CONTENT: This article is linked to Flint et al papers. To view these articles, visit https://doi.org/10.1111/apt.16608 and https://doi.org/10.1111/apt.16641